2020
DOI: 10.1007/978-981-15-4814-7_13
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Reemergence of Severe Acute Respiratory Syndrome (SARS) Coronaviruses

Abstract: The positive-strand RNA viruses, severe acute respiratory syndrome coronavirus (SARS-CoV) and recently emerged COVID-19 epidemics, demonstrated the transmission capability of the coronaviruses by crossing the species barrier and emergence in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…4,10 Thus, the lungs, immune organs, and systemic small vessels are the main targets of virus attack, so that extensive consolidation of the lung, diffuse alveolar damage with hyaline membrane formation, respiratory distress, and decreased immune function are the main causes of death. 4,10,11 On the other hand, present study showed that sepsis occurred in nearly 25% of adults due to viral infection which results in alveolar and acute respiratory failure. 12 Thus, some studies show that the main causes of death are related to SARS and sepsis, but the evolution of pulmonary and systemic inflammation in the first and/or second week may determine outcome of disease (death or survival).…”
Section: Discussionmentioning
confidence: 61%
“…4,10 Thus, the lungs, immune organs, and systemic small vessels are the main targets of virus attack, so that extensive consolidation of the lung, diffuse alveolar damage with hyaline membrane formation, respiratory distress, and decreased immune function are the main causes of death. 4,10,11 On the other hand, present study showed that sepsis occurred in nearly 25% of adults due to viral infection which results in alveolar and acute respiratory failure. 12 Thus, some studies show that the main causes of death are related to SARS and sepsis, but the evolution of pulmonary and systemic inflammation in the first and/or second week may determine outcome of disease (death or survival).…”
Section: Discussionmentioning
confidence: 61%
“…Thus, recombination among several SARS-CoV-2 variants could occur under suitable conditions favoring the emergence of new strains. The antigenic divergence of SARS-CoV-2 characterized by new glycosylation sites may have contributed to this virus generating the COVID-19 pandemic [74].…”
Section: Antigenic Changes In Sars-cov-2mentioning
confidence: 99%
“…The first complete genome sequence of the SARS-CoV-2 isolated from human cases from China was reported on January 05, 2020 by China ( Wu et al, 2020b ) and currently, thousands of genomes sequences have been reported till date. The various scientific investigations has reported that both times COVID-19 patients were infected with the viruses had differences in some of their genes caused by antigenic drift, antigenic shift, and recombination known as natural mutations ( Baxi and Saxena, 2020 ). The Hong Kong case provides the first documentary evidence and confirmed that different viral strains are responsible for reinfection ( To et al, 2020 ).…”
Section: Reinfection and Genome Sequencementioning
confidence: 99%